Integrating mental health into primary health care: local initiatives from Uganda - Ovuga, Emilio; Boardman, Jed; Wasserman, Danuta (World Psychiatry, 2007)
Uganda has passed through political and bloody civil strife stretching over 40 years. Since 1987 the HIV/AIDS pandemic has compounded the problems of the country. The present paper describes some initiatives to develop mental health services in one district of the country. A bottom-up approach in the district resulted in the formation of a community-led mental health program with strong support from two self-help groups, district political leaders and district representatives in parliament. Primary health care providers at all levels of health care in the district were trained in order to make services accessible to the rural population. Further plans based on initial exploratory discussions aim to involve the education department, the welfare and probation office, prisons and police, the military, church and cultural leaders and traditional healers. These initiatives show that it is possible to empower communities to participate in the development of mental health programs in a low-income country.
Keywords: Integration; Mental health; Primary health care